The physics of communication Contributions to the XXII Solvay Conference on Physica Delphi and Lamia, Greece, 24-29 November 2001 - Antoniou I.; Sadovnichy V. A.; Walther H. (Москва, Изд-во Московского ун-та, 2003)
All rights reserved. This work may not be translated or copied in whole or in part without the written permission of the publisher, except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or descriptive names, trade names, trademarks, etc., in this publication, even if the former are not especially identified, is not to be taken as a sign that such names, as understood by the Trade Marks and Merchandise Marks Act, may accordingly be used freely by anyone.